FERMT1 promoter mutations in patients with Kindler syndrome. (7th October 2014) - Has, C.; Chmel, N.; Levati, L.; Neri, I.; Sonnenwald, T.; Pigors, M.; Godbole, K.; Dudhbhate, A.; Bruckner‐Tuderman, L.; Zambruno, G.; Castiglia, D.
<x xml:space="preserve">Abstract</x> Mutations in the FERMT1 gene, encoding the focal adhesion protein kindlin‐1 underlie the Kindler syndrome (KS), an autosomal recessive skin disorder with a phenotype comprising skin blistering, photosensitivity, progressive poikiloderma with extensive skin atrophy, and propensity to skin cancer. The FERMT1 mutational spectrum comprises gross genomic deletions, splice site, nonsense, and frameshift mutations, which are scattered over the coding region spanning exon 2–15. We now report three KS families with mutations affecting the promoter region of FERMT1. Two of these mutations are large deletions (∼38.0 and 1.9 kb in size) and one is a single nucleotide variant (c.‐20A>G) within the 5′ untranslated region (UTR). Each mutation resulted in loss of gene expression in patient skin or cultured keratinocytes. Reporter assays showed the functional relevance of the genomic regions deleted in our patients for FERMT1 gene transcription and proved the causal role of the c.‐20A>G variant in reducing transcriptional activity.